2017
DOI: 10.1016/j.ejbas.2017.07.005
|View full text |Cite
|
Sign up to set email alerts
|

Anti-cancer potential of a mix of natural extracts of turmeric, ginger and garlic: A cell-based study

Abstract: Cancer related morbidity and mortality is a major health care concern. Developing potent anti-cancer therapies which are non-toxic, sustainable and affordable is of alternative medicine. This study was designed to investigate the aqueous natural extracts mixture (NE mix) prepared from common spices turmeric, ginger and garlic for its free radical scavenging potential and anti-cancer property against human breast cancer cell lines (MCF-7, ZR-75 and MDA-MB 231). Qualitative analysis of their bioactive constituen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 50 publications
1
30
0
Order By: Relevance
“…The allicininduced reduction in proliferation also exerted a proportionate effect on metabolism in the A549 cells. This is in agreement with previous studies that demonstrated allicin-induced declines in the percentages of actively dividing MCF-7 and ZR-75 cells [20]. In another study, it was reported that the percentage of cells in G0/G1 phase decreased with increase in the S phase population of chondrocytes when lung cancer cells were exposed to allicin [8].…”
Section: Discussionsupporting
confidence: 93%
“…The allicininduced reduction in proliferation also exerted a proportionate effect on metabolism in the A549 cells. This is in agreement with previous studies that demonstrated allicin-induced declines in the percentages of actively dividing MCF-7 and ZR-75 cells [20]. In another study, it was reported that the percentage of cells in G0/G1 phase decreased with increase in the S phase population of chondrocytes when lung cancer cells were exposed to allicin [8].…”
Section: Discussionsupporting
confidence: 93%
“…Ju and coworkers have found that administration of [6]‐gingerol inhibits tumor growth in several types of murine tumors, such as B16F1 melanomas, Renca renal cell carcinomas, and CT26 colon carcinomas, in mice (Ju et al, ). A mixture of aqueous extracts from turmeric, ginger, and garlic showed free radical scavenging potential and anticancer properties against human breast cancer cell lines (MCF‐7, ZR‐75, and MDA‐MB 231) (Vemuri et al, ). The extract additionally induced apoptosis in all the breast cancer cell lines by altering the expression of apoptotic markers (p53 and caspase 9).…”
Section: Introductionmentioning
confidence: 99%
“…The extract additionally induced apoptosis in all the breast cancer cell lines by altering the expression of apoptotic markers (p53 and caspase 9). Moreover, this extract showed a synergistically enhanced proapoptotic effect when used in combination with tamoxifen as compared with the extract alone (Vemuri et al, ). Components of ginger when used in formulations of novel products may serve for the purpose of pharmacological prevention of diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Degenerated human NPCs were cultured in 60 mm dishes and initially treated with LPS (10 ÎŒg/mL) for 24 hours. Later, anti-inflammatories Cur (10 ÎŒg/mL) and Dexa (10 ÎŒg/mL) and a combination of Cur and Dexa (10 ÎŒg/mL) were added to cells, harvested after 36 hours, prepared for cell proliferation probing with propidium iodide for 15 to 20 minutes in the dark at room temperature, and estimated using an Attune NxT flow cytometer (Applied Biosystems, Foster City, CA, USA) as per manufacturer's instructions [25,26].…”
Section: Cell Cycle Studies By Flow Cytometrymentioning
confidence: 99%